Hubungan antara tingkah laku keibubapaan, tekanan psikologikal dengan tahap kesihatan mental dalam kalangan penjaga kanak-kanak autisme - Mohd Suhaimi Mohamad,; Nur Natasha Amelia Rosdi, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper aims to identify the relationship between parenting behavior, psychologically stress and mental health among caregivers of children diagnosed with Autism at The National Autism Society of Malaysia (NASOM). One hudred caregivers consists of 50 men and 50 women has been recruited as respondents for this study. All respondents were given a set of questionnaire contained 3 instruments such as Parenting Behaviour Scale, General Health Questionaire (GHQ-12) and Mental Health Inventory (MHI). A data analysis was perfomed using Statistical Package for Social Science (SPSS) version 21. Based on research findings, the parenting behavior of children with Autism was more on the controlling side rather than other types of behavior. The levels of psychological distress among caregivers of children with Autism were high and their mental health scores were low. There were significant negative relationships between parenting behavior and mental health at the p value <0.05. Meanwhile, there was also negative relationship between psychological distress and mental health among caregivers of children with Autism in NASOM at p value <0.001. In general, it is important to assess caregiver’s parenting behavior, psychological distress and mental health status once they have been identified as a main caregiver for children with Autism. All parties include government agencies and non-government agencies like NASOM need to advocate people living with Autism children. In order to achieve it, our ministry of health or other related party need to implement new programme consists of symptoms and preventive action as an input for this caregivers about mental health care.